Stressors and normalized stress in undergraduate engineering education culture: development of the Engineering Stress Culture Scale and Undergraduate Engineering Stressors Questionnaire - Joseph F. Mirabelli; Eileen M. Johnson; Sara R. Vohra; Jeanne L. Sanders; Karin J. Jensen (International Journal of STEM Education)
Abstract Background Undergraduate engineering students report increased rates of mental health distress. Evidence suggests that these students experience high stress, which can perpetuate mental health challenges. Further, engineering students may engage in help-seeking and self-care activities more rarely than students in other disciplines. We hypothesize the existence of a culture of high stress that is normalized and expected by undergraduate engineering students. We leveraged interviews previously conducted by our team to develop two survey measures: (1) the Engineering Stress Culture (ESC) Scale, which measures cultural norms and expectations surrounding stress, and (2) the Undergraduate Engineering Stressors Questionnaire (U-ESQ), which measures factors that contribute to undergraduate engineering student stress experiences (stressors). Results We developed a novel, exploratory battery of items to measure students’ experiences with stress in undergraduate engineering education. After administering the new 81-item survey (N = 624) comprising both the U-ESQ and ESC Scale, we performed exploratory factor analysis and tested the internal consistency for each factor subscale. We then refined the survey to 58 items and administered it to a second sample of participants (N = 561) at a second institution for confirmatory factor analyses. We present evidence that the ESC Scale is a valid and reliable instrument for measuring an engineering stress culture. The final factor structure of the U-ESQ revealed eight distinct factors, each representing different stressors such as competition or identity-related experiences. We provide validity evidence for the U-ESQ. While the confirmatory evidence of the reliability of the U-ESQ instrument is less robust compared to the ESC Scale, there is acceptable evidence of reliability. This may be partially attributed to the inclusion of career-related and faculty-interaction-related stressors that may become more for salient later-stage undergraduate students, who are undersampled in our results. Conclusions We present validity and reliability evidence for the developed measures that quantify engineering student stressors and the associated high-stress culture. These measures may apply to students in other non-engineering STEM disciplines, warranting future investigations. The developed measure is a first step towards identifying and dismantling a culture of stress in engineering, which will promote student well-being and thriving.